Livelihood Vulnerability of the Informal Food Sector to Climate Extremes in Camarines Sur, Philippines - Hanilyn A. Hidalgo (Scopus ID: 57194588352) (SEAS (Sustainable Environment Agricultural Science), 2019)
The informal food sector is regarded as a huge contributor in local economic development. However, since they directly get their supplies and raw materials from agricultural produce in the local markets, they become vulnerable to the uncertainties of nature. The purpose of the study is to assess the level of livelihood vulnerability of the informal food sector as an input in enhancing the livelihood resiliency of the informal food sector in Camarines Sur, Philippines. The study uses and modifies the existing livelihood vulnerability index where seven indicators are used in determining the vulnerability: socio-demographic profile, livelihood strategies, social network, health security, food security, access to utilities, and disaster experience. The data is composed of a random sample of 200 informal food enterprises from three market areas in Camarines Sur. The livelihood vulnerability index is used to describe the vulnerability level. The study reveals a low to moderate vulnerability level of the informal food enterprises. The result is attributable to their ability to withstand disaster experience and high adaptive capacity to areas such as livelihood diversification, years in business experience and income factor. Findings suggest the need to highlight technical and social areas for intervention to further enhance their business resiliency to climate extremes.